2003
DOI: 10.1038/sj.onc.1206511
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the p53 mutants ability to inhibit p73β transactivation using a yeast-based functional assay

Abstract: p53 is the most frequently altered tumor suppressor gene in a wide spectrum of human tumors. The large majority of p53 mutations observed in tumors are missense mutations. The p73 gene, encoding a protein with significant sequence similarity to p53, expresses multiple transcription-competent spliced variants, or transcriptionincompetent forms (i.e. DNp73). It was clearly shown that p73 transactivation from a p53-responsive promoter is inhibited by some tumor-derived p53 mutants in eucaryotic cells. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…This mutation has been previously reported as a somatic mutation in breast, ovary, kidney, and stomach cancers [12][13][14]. The functional effects of missense mutations for codon 283 have been confirmed [15][16][17][18][19][20][21][22][23]. The proband, of Italian ethnic origin, was diagnosed with breast cancer at age 29 and with ovarian cancer at age 56 (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…This mutation has been previously reported as a somatic mutation in breast, ovary, kidney, and stomach cancers [12][13][14]. The functional effects of missense mutations for codon 283 have been confirmed [15][16][17][18][19][20][21][22][23]. The proband, of Italian ethnic origin, was diagnosed with breast cancer at age 29 and with ovarian cancer at age 56 (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…In the assay, p73 REs are used as upstream enhancers of the expression of a firefly luciferase gene controlled by a minimal promoter and cloned into a constant chromosomal location in isogenic yeast strains that naturally do not contain a p73 homolog (13). In experiments with yeast cells, we previously demonstrated that human p73β protein can act as a transcription factor using constitutive and inducible promoters (29). Hence, we tested the ability of human p73β to induce the expression of the luciferase gene under the enhancer control of 10 REs with spacers from 0 to 4 bp that are variations of the three half-site sequences used for crystallization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is one of hotspots in p53 mutations and has a dominant-negative activity. On the contrary, the mutation in codon 270 (exon 8) in Case 2 is extremely rare and there have been very few reports on it [17,18]. This mutation has not dominant-negative activity [17] and inhibits recessively transactivation of p73 by binding to p73 [18].…”
Section: Discussionmentioning
confidence: 98%
“…On the contrary, the mutation in codon 270 (exon 8) in Case 2 is extremely rare and there have been very few reports on it [17,18]. This mutation has not dominant-negative activity [17] and inhibits recessively transactivation of p73 by binding to p73 [18]. Narita et al described germline mutations of p53 at exon 4-9 were not detected in a female patient with malignant fibrous histiocytoma, whose son and daughter developed liposarcomas [8].…”
Section: Discussionmentioning
confidence: 99%